Caring for parturient: a vision of nursing students - Francisca Ana Martins Carvalho; Ana Karine Bezerra Pinheiro; Lorena Barbosa Ximenes (Rev Rene)
We aimed to understand the meaning of witnessing a child birth in the nursing students’ point of view. For our research we decided for the qualitative approach. We also chose the theoretical perspective of Symbolic Interactionism as well as a thematic analysis. The subjects who participated in the study were twenty Nursing scholars who experienced obstetric practice. To collect data it was used the participant observation and open interview to understand the possible signifi cance of birth for the scholars of Nursing from the theme: birth – the discovery of a new life. We understand that scholars demystify the beliefs as well as values concerning natural birth. For them to attend a birth is a situation which involves expectation, anxiety and suffering but that also causes delight.